-(2x+7y)-4x+(3x-4y)=

Simple and best practice solution for -(2x+7y)-4x+(3x-4y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2x+7y)-4x+(3x-4y)= equation:


Simplifying
-1(2x + 7y) + -4x + (3x + -4y) = 0
(2x * -1 + 7y * -1) + -4x + (3x + -4y) = 0
(-2x + -7y) + -4x + (3x + -4y) = 0

Remove parenthesis around (3x + -4y)
-2x + -7y + -4x + 3x + -4y = 0

Reorder the terms:
-2x + -4x + 3x + -7y + -4y = 0

Combine like terms: -2x + -4x = -6x
-6x + 3x + -7y + -4y = 0

Combine like terms: -6x + 3x = -3x
-3x + -7y + -4y = 0

Combine like terms: -7y + -4y = -11y
-3x + -11y = 0

Solving
-3x + -11y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11y' to each side of the equation.
-3x + -11y + 11y = 0 + 11y

Combine like terms: -11y + 11y = 0
-3x + 0 = 0 + 11y
-3x = 0 + 11y
Remove the zero:
-3x = 11y

Divide each side by '-3'.
x = -3.666666667y

Simplifying
x = -3.666666667y

See similar equations:

| 3x-4.7=2.8 | | 3(y-6)/5=-3y | | (x+2)(x+3)=2x-10 | | (-12)(-10)= | | 15y+14=2(5y+6y) | | (16)(28)(2)= | | 5c-4c+c-3c= | | -3(5)(2)(-3)= | | 2.5x+50=80 | | 3a+(2a+6)= | | x/2+1=4-x | | x-.14(x)=250.00 | | 8b+8-4b-3= | | 5(4x-2)-5(3x-19)=2(2x+1)-1 | | x^2+-32x+220=0 | | 0.5(x+50)+0.5x=50 | | (-2)(6)(-5)= | | x-.14(x)=275.00 | | (-10)(-10)= | | 8p-9p=72 | | (-5)*(5)= | | -6p-9=-11-5p | | 3a+6+5a-2= | | -3x+(2x-3)= | | F=1/2(r+6.5) | | ln(3x-8)+ln(x-4)=2lnx | | p/8=20 | | 77=x+50 | | 16-5e=15.5 | | -(-2x-4)-x= | | 3a+6+5a-2 | | 22x-11=13x+7 |

Equations solver categories